Performance evaluation of dense-graded asphalt mixture for high-strength application - Ubanan, Hazel Nina Pinero (Nanyang Technological University, 2023)
In Singapore, a densely populated and resource-scarce city-state, the need for safe and reliable road infrastructure is paramount. With a growing population and thousands of vehicles using the road network, ongoing maintenance is crucial to minimise deterioration and ensure road safety. The fiscal report of 2021 revealed significant government spending on road improvements and infrastructure, aiming to enhance accessibility and reduce traffic congestion across the island. Given the rising costs of road construction materials, exploring cost-effective alternatives such as alternate aggregates are essential. Aggregates are to provide a strong bond with bitumen, resulting in excellent road quality, skid resistance, and resistance to cracks. In this study, three different gradation mixes, namely W3B, W3, and W1, were evaluated based on LTA’s Marshall Design Criteria to reaffirm that the mix design is suitable for use for the construction of pavements for high-strength applications in Singapore. The study also involved the evaluation of the use of granite fillers instead of hydrated lime fillers, to understand the influence of hydrated lime fillers on the mechanical properties and long-term performance of the mixes. The project methodology of this study also served as fundamental comprehension for the research approach and goals associated with assessing an asphalt concrete mixture. It is to offer a thorough evaluation, encompassing various performance tests such as the Marshall Test, Moisture Susceptibility Test, Creep Resistance Test, and Indirect Tensile Test. Ultimately, this study seeks to appraise the performance and attributes of the asphalt concrete mixture. Based on the study's data and analysis, W3B emerged as the top-performing gradation mix. It demonstrated alignment with the theoretical expectations of the performance tests, characterised by a well-balanced distribution of coarse and fine aggregates, contributing to higher strength and durability. Furthermore, W3B exhibited reduced susceptibility to rutting compared to W3 and W1, thereby enhancing its durability and the safety of the pavement surface.